2005
DOI: 10.1093/ndt/gfh1090
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-mediated pure red cell aplasia (PRCA) treatment and re-treatment: multiple options

Abstract: In the vast majority of patients with antibody (Ab)-mediated pure red cell aplasia (PRCA), simple withdrawal of the erythropoiesis-stimulating agent (ESA) does not effectively reverse PRCA. In contrast, immunosuppressive treatments can induce the disappearance of anti-erythropoietin Abs and a reversal of PRCA. Consensus opinion on the optimal therapy has not been established, but individual case reports or case series suggest that kidney transplantation or treatment with corticosteroids plus cyclophosphamide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…Therefore, one study recommended that a successful therapeutic strategy for patients with anti-EPO PRCA should consist of stopping administration of all ESAs and initiating cyclosporine therapy. However, if cyclosporine does not increase reticulocyte (Ret) counts, treatment with other immunosuppressive drugs, such as corticosteroids plus cyclophosphamide, or kidney transplantation should be considered [7]. Tacrolimus and cyclosporine are calcineurin inhibitors, with similar pharmacological functions but different receptors [8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, one study recommended that a successful therapeutic strategy for patients with anti-EPO PRCA should consist of stopping administration of all ESAs and initiating cyclosporine therapy. However, if cyclosporine does not increase reticulocyte (Ret) counts, treatment with other immunosuppressive drugs, such as corticosteroids plus cyclophosphamide, or kidney transplantation should be considered [7]. Tacrolimus and cyclosporine are calcineurin inhibitors, with similar pharmacological functions but different receptors [8].…”
Section: Introductionmentioning
confidence: 99%
“…Early recognition of PRCA and withholding of ESA therapy are essential, but cessation of ESA treatment alone generally will not cure ESA-induced PRCA (25). In cases of PRCA induced by other drugs (unrelated to anti-erythropoietin antibody production), the PRCA generally remits within 1 to 2 wk after elimination of exposure to the causative agent.…”
Section: Treatment Of Esa-induced Prcamentioning
confidence: 99%
“…Verhelst et al (29) reported higher recovery rates when corticosteroids were given together with cyclophosphamide (87%) than when corticosteroids were given alone. In patients with CKD and ESA-induced PRCA, oral cyclosporine therapy resulted in hematologic recovery in more than two thirds of the investigated PRCA cases (25). Of 15 patients with idiopathic PRCA treated with a humanized mAb to the IL-2 receptor (daclizumab), six (40%) responded to the treatment, but this therapy has not been evaluated in patients with antibody-mediated PRCA (30).…”
Section: Treatment Of Esa-induced Prcamentioning
confidence: 99%
“…While there are only a handful of cases reported in the literature in which this has been attempted [27][28][29], it does appear that successful rechallenge is possible, particularly if immunosuppression is continued to inhibit antibody production. There is at least one case, however, of relapse of antibody-mediated PRCA after rechallenge [30], and the possibility that this may occur should be recognized.…”
Section: Management Of Epoetin-induced Pure Red Cell Aplasiamentioning
confidence: 99%